President Pratibha Devisingh Patil : selected speeches - Patil, Pratibha (New Delhi Ministry of Information and Broadcasting, 2012)
The present volume is a compilation of the speeches of Smt. Pratibha Devisingh Patil, the twelfth President and the first woman President in the history of democratic India. Her speeches covering the period between July 2007 to December 2008 lay emphasis on the effort that needs to be made for protection of the fundamental rights of the people and to ensure human dignity to all.
Volume 1. July2007-December 2008.
Keywords: Politics and government; President of India; Pratibha Devisingh Patil